2021
DOI: 10.1371/journal.pone.0245086
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of metabolic syndrome and its components in adults with psychotic disorders in Eldoret, Kenya

Abstract: Background A high prevalence of metabolic syndrome and its components in patients with psychotic disorders may increase the risk for cardiovascular diseases. Unfortunately, relatively little work in this field has emerged from low-resourced contexts. This study investigated the prevalence, correlates, and treatment patterns of metabolic disorders in patients with psychotic disorders in Western Kenya. Methods 300 patients with psychosis and 300 controls were recruited at Moi Teaching and Referral Hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
1
4
1
Order By: Relevance
“…Although females were more likely to have a higher percentage of overweight than males, statistically, this was not significant. This finding does differ from the one that was found in a study done by Kwobah and colleagues, which showed that 45% of the patients with a psychiatric disorder were obese as compared to normal individuals who were not suffering from psychotic disorders [40]. In terms of waist circumferences, 42.2% of the study population had higher waist circumferences.…”
Section: Waist Circumferencecontrasting
confidence: 85%
“…Although females were more likely to have a higher percentage of overweight than males, statistically, this was not significant. This finding does differ from the one that was found in a study done by Kwobah and colleagues, which showed that 45% of the patients with a psychiatric disorder were obese as compared to normal individuals who were not suffering from psychotic disorders [40]. In terms of waist circumferences, 42.2% of the study population had higher waist circumferences.…”
Section: Waist Circumferencecontrasting
confidence: 85%
“…Notably, 56.2% of medical service patients do not undergo medical monitoring, nor are they evaluated by a psychiatrist during service. This therapeutic inertia has already been described by other groups [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 60%
“…For instance, in a study carried out in South Africa on 278 subjects with severe mental illness, the estimated prevalence of MetS was 23.2% [ 31 ]; whereas, in the middle belt of Ghana 14.1% [ 32 ]. The report from Kenya was slightly higher at 28.6% [ 33 ]. Three studies conducted in the central, south, and western part of the Ethiopia among patients with psychiatric illness, diagnosed with schizophrenia, major depressive disorder, bipolar disorder and others, reported prevalence of MetS ranged from 18 to 25% [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%